2019
DOI: 10.4103/aer.aer_75_19
|View full text |Cite
|
Sign up to set email alerts
|

Patient transportation delays and effects on operation theatres' efficiency: A study for problem analysis and remedial measures

Abstract: Background and Aims:Delay in patients’ transportation to the operating theater (OT) is a globally recognized phenomenon, leading to delay in the subsequent processes (anesthesia induction, surgery, and patient turnover). This observational study was conducted to evaluate the common reasons for delay in transporting patients to the neurosurgery OT complex and its consequent effects and how the elimination of these reasons by application of feasible measures can influence the after effects.Settings and Design:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Lack of ease of accessibility of main theatres from the surgical wards and ICU was significantly associated with delays. This is similar to a study by Haldar, et al [23].…”
Section: Multinomial Logistic Regression Test On Factors Affecting Tatsupporting
confidence: 93%
See 2 more Smart Citations
“…Lack of ease of accessibility of main theatres from the surgical wards and ICU was significantly associated with delays. This is similar to a study by Haldar, et al [23].…”
Section: Multinomial Logistic Regression Test On Factors Affecting Tatsupporting
confidence: 93%
“…This mirrors a study conducted in Malawi which indicated that there were few staff and too many patients leading to 40% wanting to resign [27]. There were few patient porters causing delays in movement to and from theatre; similarly observed by Haldar, et al [23]. Studies have shown that staff collaboration and teamwork between staff and management were associated with decreased delays in theatres [27,28].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Studies categorized into this group described interventions that involved redesigning an entire process with multiple individuals and steps. These interventions often employed parallel processing, 9,16,20,21,26–30 redefining/clarifying roles, 12,16,17,22,30–32 reducing nonvalue‐add steps, 16,19–21,30 and standardization of tasks 27,30,33 . This was the most common intervention strategy utilized and was associated with reduced TOT in all but one study 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Process redesign bundle. WORLD JOURNAL OF SURGERY parallel processing, 9,16,20,21,[26][27][28][29][30] redefining/clarifying roles, 12,16,17,22,[30][31][32] reducing nonvalue-add steps, 16,[19][20][21]30 and standardization of tasks. 27,30,33 This was the most common intervention strategy utilized and was associated with reduced TOT in all but one study.…”
Section: Intervention Detailsmentioning
confidence: 99%